Motivación Al Talento Humano De La Fundación Teolinda Troya - Villalva Cabezas, Narcisa Esther (2017)
With all the evidence in the company can be verified that the most important asset of the TEOLINDA TROYA E Foundation is its human resource; since the world demands of this greater preparation, fidelity with the institution and the capacity to adapt to the changes that globalization demands day by day. Many companies do not give necessary importance to the factor that can help to increase the productivity and development of the organization as it is the motivation to the personnel